Production of value-added broiler nugget enriched with dietary fiber from oat meal (Bangladesh Journal of Animal Science, 2020)
An experiment was conducted to find out the effect of oat meal as a source of dietary fiber to formulate enriched broiler nugget. For this purpose, nuggets were prepared into four different groups such as treatment 1: 10% wheat flour nugget, treatment 2: 20% wheat flour nugget, treatment 3:10% oat meal nugget and treatment 4: 20% Oat meal nugget. All parameters were analyzed at 0, 15th and 30th days of storage period. The proximate composition of different nuggets batter was analyzed and highly significant differences were found in dry matter (%) and pH. Dry matter was lower, while pH was higher in control nugget (Treatment 1). Significant differences were found in crude protein (%), ether extract (%) among different nuggets, as well as among different storage time. Significantly higher DM (%), Ash (%) and EE (%) was found in broiler meat with 20% oat meal, while higher crude protein (%) were found in broiler meat+10% wheat flour. Crude protein (%) and DM (%) increased, while Ash (%) and EE (%) decreased with increase of storage time.  The storage period had significant effect on different biochemical (FFA, POV and TBARS value) and microbial (TVC, TCC and TYMC) tests. In all cases, the values were increased with increase of storage time. The surface color (CIE L*, a*, b*) of nuggets of different treatments at different storage period were measured.  No significant differences in b* value were found among broiler meat nuggets and storage time. On the other hand, different types of nuggets and storage period had a significant effect on L* and a* value. Significantly higher a* value was found in broiler meat with 10% wheat flour (T1). In sensory analysis, no significant differences were found in flavor, off-flavor, juiciness, tenderness and overall acceptability among four types of sausages. It could be concluded that addition of oat meal as a source of dietary fiber did not differ the overall acceptability of broiler meat nuggets compare to broiler meat nuggets with wheat flour.Bang. J. Anim. Sci. 2020. 49 (1): 71-82